The Bacterial and Fungal Microbiota of “Robiola di Roccaverano” Protected Designation of Origin Raw Milk Cheese - Biolcati, Federica; Ferrocino, Ilario; Bottero, Maria Teresa; Dalmasso, Alessandra (Frontiers in Microbiology, 2022)
Robiola di Roccaverano is an artisanal Protected Designation of Origin (PDO) soft cheese made with raw goat’s milk and by the addition of Natural Milk Culture (NMC) to drive the fermentation process. Cheeses collected from five different dairy plants were analyzed for their bacterial and fungal microbiota diversity. Lactococcus lactis and Leuconostoc mesenteroides were the main bacterial population while Galactomyces candidum and Kluyveromyces marxianus constituted the core mycobiota but many other minor taxa were observed, suggesting a high level of complexity in fungal composition by these cheeses compared to bacteria population.